Identifying regulatory outcomes of Non-interventional Post-Authorisation Safety Studies (PASS) in the European repository of studies using publicly available information - Almas, M. F.; Girardi, A.; Crisafulli, S.; Gvozdanovic, K.; Hakkarainen, K. M.; Hyeraci, G.; Hoogendoorn, W. E.; Rillmann, B.; Roberto, G.; Vitturi, G.; Trifirò, G., ENCePP WG3 (Frontiers in Drug Safety and Regulation, 2025)
BackgroundPost-Authorisation Safety Studies (PASS) generate evidence that may support regulators to evaluate the benefit-risk profile of medicinal products and to take regulatory actions when needed. The European Medicine Agency (EMA) promoted decision-making transparency by publishing regulatory guidelines and endorsing the registration of PASS in the European Post‐Authorisation Study (EU PAS) Register (currently HMA-EMA Catalogues of real-world studies). A recent analysis of the EU PAS Register showed a marked increase of PASS conducted as multidatabase studies (MDS) during the last decade.PurposeThis study aimed to assess the feasibility of using public available information from the EMA website to identify regulatory outcomes of PASS and, to describe the retrieved regulatory outcomes of PASS by MDS and non-MDS.MethodsMultidatabase PASS, and an equal number of non-multidatabase PASS, were selected from the EU PAS Register if: completed between 07/2012 and 12/2020, part of the Risk Management Plan (RMP) category 1,2 or 3, required by an European regulator, and conducted in ≥1 European country including United Kingdom (UK). Mentions of the identified PASS were searched in the Pharmacovigilance Risk Assessment Committee (PRAC) meeting minutes, the procedural steps document of the European Public Assessment Report (EPAR), and other publicly available EMA webpages, mainly using study title, acronym, protocol, or regulatory number. Whenever identified, the regulatory outcome information was retrieved.ResultsA total of 84 PASS (42 MDS and 42 non-MDS) were included in the analysis. We could identify 77% of the 84 PASS in at least one of the used sources but the information available was scarce. Among the identified PASS, information on regulatory outcomes was identified for 60%, representing 46% of all 84 PASS, with no differences between MDS and non-MDS. Regulatory outcome information was more frequently identified for imposed (78%) than non-imposed PASS (34%). The availability of regulatory outcomes increased from 25% for PASS completed in the years 2012–2014 to 56% for those completed in 2018–2020. The regulatory outcome information was unspecific for two thirds of the PASS with available outcomes, limiting our description of regulatory outcome types.ConclusionThe attempt to identify and describe the regulatory outcomes of MDS registered into the EU PAS Register, and compare them to non-MDS, was impaired by the difficulties in retrieving the regulatory outcome insights from the publicly available sources such as, identifying PASS across sources, lack of information and granularity, standardisation and consistency across sources. We advocate for an increased transparency of the regulatory outcomes of PASS through the use of a unique PASS identifier for an easy link across sources, and for a complete regulatory outcome publication with enhanced and standardised presentation of regulatory outcomes to understand the regulatory impact of the PASS.